2015
DOI: 10.1111/zoj.12303
|View full text |Cite
|
Sign up to set email alerts
|

Three ways to distinguish species: using behavioural, ecological, and molecular data to tell apart two closely related ants,Camponotus renggeriandCamponotus rufipes(Hymenoptera: Formicidae)

Abstract: The closely related Camponotus renggeri and Camponotus rufipes (subgenus Myrmothrix) often live in sympatry in the Brazilian 'cerrado' savannah, and are distinguished by nuances in their blackish body colour and by the colour of the legs. Variation in morphological characters, however, makes species separation difficult and it has been suggested that the two species should be merged into one. As appropriate species identification is essential for studies in ecology and evolutionary biology, here we examine how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 58 publications
3
30
0
4
Order By: Relevance
“…Our study reinforces the importance of an integrative approach for the correct delimitation of closely related species, as Ronque et al () succeeded in other insects. By combining morphological features concerning the stridulatory apparatus with behavioral and molecular data, we have shown that there are clear differences between the two studied “species” of Sinipta and confirmed that S. dalmani and S. hectorisperonii are distinct species.…”
Section: Discussionsupporting
confidence: 89%
“…Our study reinforces the importance of an integrative approach for the correct delimitation of closely related species, as Ronque et al () succeeded in other insects. By combining morphological features concerning the stridulatory apparatus with behavioral and molecular data, we have shown that there are clear differences between the two studied “species” of Sinipta and confirmed that S. dalmani and S. hectorisperonii are distinct species.…”
Section: Discussionsupporting
confidence: 89%
“…Altogether, this study is based on specimens from over 118 litter samples, 78 pitfall traps, 228 surface baits, 57 underground baits, and 348 hand‐collecting events. Collected ants were preserved in ethanol 96% and identified using the available literature (Boudinot, Sumnicht, & Adams, ; Brown, ; Dash, ; Fernandes, De Oliveira, & Delabie, ; Jiménez, Fernández, Arias, & Lozano‐Zambrano, ; Kempf, , ; Kugler & Brown, ; Lattke, Fernández, & Palacio, ; Lenhart, Dash, & Mackay, ; Longino & Fernández, ; MacKay, ; Mackay, & Mackay, ; Ortíz Sepúlveda, ; Ronque, Azevedo‐Silva, Mori, Souza, & Oliveira, ; Wild, , ). If we were unable to key out specimens reliably to species, they were assigned to a morphospecies.…”
Section: Methodsmentioning
confidence: 99%
“…Collected ants were preserved in ethanol 96% and identified using the available literature (Boudinot, Sumnicht, & Adams, 2013;Brown, 1978;Dash, 2011;Fernandes, De Oliveira, & Delabie, 2014;Jiménez, Fernández, Arias, & Lozano-Zambrano, 2008;Kempf, 1962Kempf, , 1965Kugler & Brown, 1982;Lattke, Fernández, & Palacio, 2007;Lenhart, Dash, & Mackay, 2013;Longino & Fernández, 2007;MacKay, 1996;Mackay, & Mackay, 2010;Ortíz Sepúlveda, 2012;Ronque, Azevedo-Silva, Mori, Souza, & Oliveira, 2015;Wild, 2005Wild, , 2007b). If we were unable to key out specimens reliably to species, they were assigned to a morphospecies.…”
Section: Ant Surveysmentioning
confidence: 99%
“…The recent study conducted by Ronque et al (2015) based in an integrative approach showed very useful in understanding taxonomic issues of C. rufipes and C. renggeri. The lack of variation in the amount of DNA between these two Camponotus ants indicated that these species could not be distinguished based solely on genome size, highlighting the importance of additional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the path of chromosome evolution of three species with distinct degrees of relatedness should provide further information in enriching our knowledge about the Minimum Interaction Theory. (Seifert, 2009;Schlick-Steiner et al, 2010), the use of integrative approach is very useful in distinguishing these species, as indicated by a recent study of Ronque et al (2015).…”
Section: Introductionmentioning
confidence: 99%